Question

solve the equation e*2*n+7*e*n-8=0

102

likes508 views

Velda

4.5

64 Answers

Pour résoudre l'équation e \cdot 2n + 7en - 8 = 0 , on commence par factoriser par regroupement :

e \cdot 2n + 7en - 8 = 0

2en + 8en - e - 8 = 0

2en(1+4) - 1(1+8) = 0

2en \cdot 5 - 1 \cdot 9 = 0

Ensuite, on factorise l'expression obtenue :

10en - 9 = 0

10en = 9

e = \frac{9}{10n}

Donc, la solution de l'équation est e = \frac{9}{10n} .

\boxed{e = \frac{9}{10n}}

Ensuite, on factorise l'expression obtenue :

Donc, la solution de l'équation est

Frequently asked questions (FAQs)

Question: What is the maximum value of the function f(x) = 2x^3 - 6x^2 + 9x on the interval [-2, 4]?

+

Question: What is the probability of rolling a perfect pair of dice, where both dice show the number 6, in two consecutive rolls?

+

Question: What is the probability of drawing a red card from a standard deck of 52 playing cards?

+

New questions in Mathematics